ANALISIS UJI IMPAK PADA PENGELASAN BAJA ST37 MENGGUNAKAN LAS SHIELD METAL ARC WELDING (SMAW) DENGAN POSISI PENGELASAN 1G - Welcy Fratama; Tuparjono Tuparjono; Erwanto Erwanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Welding is the process of joining two or more metal materials into a single unit in the presence of heat energy. SMAW (Shielded Metal Arc Welding) welding is the process of joining two or more materials using wrapped electrodes as heat energy to melt the material. In SMAW welding there is the use of layers and passes. In this study, welding with variations of pass will be carried out using SMAW welding on St37 steel with 1G welding position. The pass variations used in welding are 6 passes, 7 passes, and 8 passes. The electrodes used were 2.6 mm diameter E7016 and 3.2 mm diameter E7018 electrodes. To determine the impact of pass variations on the welding results, an impact test will be carried out. From the results of research that has been done that welding with a small number of passes has a better amount of energy than welding with a large number of passes. Likewise for the impact price, welding with a small number of passes has a better impact price than welding with a large number of passes.